Vasopressin and parental expressed emotion in the transition to fatherhood. Issue 3 (4th May 2021) - Lotz, Anna M.; Rijlaarsdam, Jolien; Witteman, Jurriaan; Meijer, Willemijn; van Dijk, Kim; van Ijzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.
ABSTRACT: In the last decades, parenting researchers increasingly focused on the role of fathers in child development. However, it is still largely unknown which factors contribute to fathers' beliefs about their child, which may be crucial in the transition to fatherhood. In the current randomized within-subject experiment, the effect of nasal administration of vasopressin (AVP) on both Five Minute Speech Sample-based (FMSS) expressed emotion and emotional content or prosody was explored in 25 prospectivefathers. Moreover, we explored how the transition to fatherhood affected these FMSS-based parameters, using prenatal and early postnatal measurements. Analyses revealed that FMSS-based expressed emotion and emotional content were correlated, but not affected by prenatal AVP administration. However, child's birth was associated with an increase in positivity and a decrease in emotional prosody, suggesting that the child's birth is more influential with regard to paternal thoughts and feelings than prenatal AVP administration.